Beta oscillations reflect memory and motor aspects of spoken word production. Issue 7 (14th April 2015) - Piai, Vitória; Roelofs, Ardi; Rommers, Joost; Maris, Eric
Abstract Two major components form the basis of spoken word production: the access of conceptual and lexical/phonological information in long‐term memory, and motor preparation and execution of an articulatory program. Whereas the motor aspects of word production have been well characterized as reflected in alpha‐beta desynchronization, the memory aspects have remained poorly understood. Using magnetoencephalography, we investigated the neurophysiological signature of not only motor but also memory aspects of spoken‐word production. Participants named or judged pictures after reading sentences. To probe the involvement of the memory component, we manipulated sentence context. Sentence contexts were either constraining or nonconstraining toward the final word, presented as a picture. In the judgment task, participants indicated with a left‐hand button press whether the picture was expected given the sentence. In the naming task, they named the picture. Naming and judgment were faster with constraining than nonconstraining contexts. Alpha‐beta desynchronization was found for constraining relative to nonconstraining contexts pre‐picture presentation. For the judgment task, beta desynchronization was observed in left posterior brain areas associated with conceptual processing and in right motor cortex. For the naming task, in addition to the same left posterior brain areas, beta desynchronization was found in left anterior and posterior temporal cortex (associated with memory aspects), left inferior frontal cortex, and bilateral ventral premotor cortex (associated with motor aspects). These results suggest that memory and motor components of spoken word production are reflected in overlapping brain oscillations in the beta band. Hum Brain Mapp 36:2767–2780, 2015. © 2015 Wiley Periodicals, Inc.